Hubungan human immunodeficiency virus/acquired immunodeficiency syndrome (HIV/AIDS) dengan kejadian penyakit kardiovaskular: konsistenkah bukti yang ada? - Fitriani, Indah; Dharmasaputra, Alan; Marshella, Sally; Rosiana, Safira; Pramesuari, Florentina Dewi; Umar, Tungki Pratama (Fakultas Farmasi Universitas Tjut Nyak Dhien, 2024)
Human Immunodeficiency Virus (HIV) and Acquired Immune Deficiency Syndrome (AIDS) pose ongoing global health challenges. This literature review evaluates the relationship between HIV infection and increased cardiovascular diseases, outlining findings from sixteen observational studies. Key findings involve an elevated risk of hypertension, coronary artery disease, sudden cardiac death, and cardiovascular risk factors among HIV patients. Additionally, antiretroviral therapy (ART) side effects are highlighted, including specific impacts of certain drugs. The gender of HIV/AIDS patients also plays a role in cardiovascular risk profiles. The study details the pathophysiological mechanisms, such as immune activation and inflammation, involved in the heightened cardiovascular risk in individuals with HIV/AIDS. This study underscores the importance of a comprehensive understanding of cardiovascular health impacts on the HIV/AIDS population to guide informed therapeutic choices for preventing cardiovascular status deterioration.